Construção de saberes, criação de fazeres: educação de jovens no hip hop de São Carlos. - Siqueira, Cristiano Tierno de (Universidade Federal de São Carlos, 2004)
This research started on March, 2002, at the Program of Post Graduation in Education (UFSCar) Concentration area: Teaching Methodology. The knowledge s construction presented here has, as co-labors, the youngsters from São Carlos Hip-Hop and the main matter of this research refers to the educative processes that permeates their quotidian, the way they educate themselves and the way they educate other persons from their communities. We had, therefore, as the aim of this study, the undestanding and the sistematization of the educative processes present at the practice of those youngsters, willing to contribute to the valorization of educational practices on Youth Movements and on elaboration of related politics . Therefore, we have followed up with their activities, as weekly meetings, artistic events, educational activities and parties. Based on those follow-ups we have gatthered material for to the elaboration of one interviewing guide, developed with four youngsters (three young men and one young woman). Data obtained were organized for analisys at the followings focuses: Hip-Hop, São Carlos Hip-Hop, the Hip-Hop doing in São Carlos, Hip-Hop and communities, Hip-Hop and Youth and São Carlos Hip-Hop s Youth education. Data analisys revealed some present values in life of those persons, as love for what each one does, the need of collective work, responsability, belonging to a community, respect, effort and criativity. Those values are ilustrated at the Rap s lirics conception, at the organization and presentation of artistic events, at the art educational workshops. All those values and actions look for the creation, the invention of a quotidian with better conditions of life, looking for disrupt the reprodution of the realities. We believe that this research brings contributions in order of thinking in education that permeates social practices in non-scholar places, and to re-think the education in scholar places.
Keywords: Educação; Práticas sociais e processos educativos; Movimento hip hop; CIENCIAS HUMANAS::EDUCACAO